Evaluasi Kinerja Karyawan Berdasarkan Career Development, Kemampuan Kerja dan Loyalitas Karyawan - Chintya Ones Charli; Mardhatila Fitri Sopali; Recy Harviani Zurwanty (J-MAS (Jurnal Manajemen dan Sains), 2022)
Performance is a reaction from a job that results from the quality or quantity aspects of the work and the responsibilities imposed by the company, as well as the skills, expertise capacity and ability to complete work within a certain time span. The purpose of this study was to evaluate employee performance based on Career Development, Work Ability and Employee Loyalty. This research was conducted at PT Semen Padang, with the number of samples used as many as 92 employees obtained based on the non-probability sampling technique. Data was collected by distributing questionnaires and the analysis technique used was regression analysis. Based on the results of the analysis, it was found that there was a significant influence between Career Development, work ability and employee loyalty on employee performance. This study shows the results that a regular career development system will foster good employee performance, good work skills will be able to help improve the performance and loyalty of an employee will have an impact on increasing employee performance. Where in this study shows that career development has a greater impact on employee work outcomes.